Analisis Instrumen Bank Syariah Terhadap ROA Pada PT Bank BCA Syariah - Sari Dewi; Nurul Istiqomah; Caesar Dharmawan; Fadilla Rahmadani; Lidiawati Lidiawati; Chrisna Chrisna; Joyce Tan (Journal of Islamic Economics and Finance, 2024)
This study aims to analyze the effect of various Islamic banking instruments on the Return on Asset (ROA) provided by PT Bank BCA Syariah. This study uses historical data for the last five years (2018-2022) and statistical analysis to evaluate the contribution of certain Islamic banking instruments to the amount of financing provided by the Islamic bank. The results of this study provide greater insight into how Islamic banking instruments affect the financing portfolio of PT Bank BCA Syariah and can serve as a foundation for future strategic decision-making in the management of Islamic banking funds and financing. This research is expected to make a positive contribution to the understanding of the development of Islamic banking and sustainable Islamic banking practices.